2023
DOI: 10.3390/jof9100979
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Traits and Azole Resistance in Korean Candida auris Isolates

Seung A. Byun,
Yong Jun Kwon,
Ga Yeong Lee
et al.

Abstract: We analyzed the virulence traits and azole resistance mechanisms of 104 Candida auris isolates collected from 13 Korean hospitals from 1996 to 2022. Of these 104 isolates, 96 (5 blood and 91 ear isolates) belonged to clade II, and 8 (6 blood and 2 other isolates) belonged to clade I. Fluconazole resistance (minimum inhibitory concentration ≥32 mg/L) was observed in 68.8% of clade II and 25.0% of clade I isolates. All 104 isolates were susceptible to amphotericin B and three echinocandins. In 2022, six clade I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In this study, we found that C. auris was frequently isolated from ear discharge, rather causing a bloodstream infection or outbreak, and the isolation of C. auris was decreased during the pandemic. This might be explained by characteristics of the East Asian clade (clade II), which were inherently different from other clades [ 19 , 30 , 31 ]. A recent study suggested that several factors such as reduced thermal tolerance at 42 °C, reduced virulence in the G. mellonella model, and a reduced competitive growth ability compared to non-clade II isolates might contribute to the decreased colonization by clade II C. auris in hospital settings and at various body sites and to their absence in nosocomial transmissions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that C. auris was frequently isolated from ear discharge, rather causing a bloodstream infection or outbreak, and the isolation of C. auris was decreased during the pandemic. This might be explained by characteristics of the East Asian clade (clade II), which were inherently different from other clades [ 19 , 30 , 31 ]. A recent study suggested that several factors such as reduced thermal tolerance at 42 °C, reduced virulence in the G. mellonella model, and a reduced competitive growth ability compared to non-clade II isolates might contribute to the decreased colonization by clade II C. auris in hospital settings and at various body sites and to their absence in nosocomial transmissions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by characteristics of the East Asian clade (clade II), which were inherently different from other clades [ 19 , 30 , 31 ]. A recent study suggested that several factors such as reduced thermal tolerance at 42 °C, reduced virulence in the G. mellonella model, and a reduced competitive growth ability compared to non-clade II isolates might contribute to the decreased colonization by clade II C. auris in hospital settings and at various body sites and to their absence in nosocomial transmissions [ 31 ]. However, further surveillance should be continued considering the recent emergence of six clade I isolates of C. auris in a Korean hospital [ 31 ], harboring the potential to be a nosocomial cluster in Korea.…”
Section: Discussionmentioning
confidence: 99%